Crosslinked polyolefin foams with large core pores
Through controlled deep crosslinking technology, the design of low crosslinking degree and large cell size in the intermediate region in polyolefin foaming body is solved, and uniform tearing and multiple properties are achieved. improve.
Patent Information
- Application Number
- CN202411796198.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-28
- Filing Date
- 2020-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The existing polyolefin foams tear unevenly during splitting, resulting in uneven foaming parts remaining on the walls and items, and are difficult to meet the performance requirements in a variety of applications.
The controlled deep crosslinking technology is adopted to make the intermediate region of the foam have a lower crosslinking degree and a larger cell size. Through this structural design, the controlled tear propagation is achieved when the splitting force is applied, so that the The first side and the second side of the foam are evenly separated.
It realizes uniform tearing of the foam during splitting, improves the structural and mechanical properties of the foam, and is suitable for a variety of applications, including improvements in acoustic performance, adhesive performance, water retention performance, etc.
Smart Images

Figure CN119431929A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application 202080081508.2, the application date of which is November 25, 2020, and the name of the invention is “Cross-linked polyolefin foam with large core holes”.
[0002] priority
[0003] This application claims priority to U.S. Patent Application Nos. 16 / 699,062 and 16 / 699,063, filed on November 28, 2019, the entire contents of which are incorporated herein by reference. Technical Field
[0004] The present invention generally relates to polyolefin foams, and more specifically to polyolefin foams with high recovery performance and cleavable large core cells and their manufacturing methods, wherein the foam has a variety of improved structural and mechanical properties, for example, both as a single foam sheet (before cleaving) and after being cleaved into two foam sheets. Background Art
[0005] The conventional method of making polyolefin foams comprises extruding a foamable sheet comprising a thermoplastic resin, a foaming agent and an additive. Before the foamable sheet is foamed in an oven at the activation temperature of the foaming agent, the foamable sheet can be crosslinked via irradiation, for example, by passing the sheet through an electron beam irradiator. As implemented in the prior art, the electron beam irradiator is used to deliver a sufficient dose of electrons to each side of the foamable sheet, thereby making these electrons pass through the material of the foamable sheet all the time and come out from the other side, while providing a uniform crosslinking level in the foamable sheet. As the electrons pass through the foamable sheet, they impart energy to the material, forming crosslinks between polymer strands, thereby enhancing adhesion throughout the thickness of the foamable sheet.
[0006] For example, in conventional methods, a foamable sheet can be passed through an electron beam irradiator so that the first side is first exposed to irradiation. The irradiator is used to deliver a sufficient dose of electrons so that the electrons pass through and through the foamable sheet from the first side and come out from the opposite side, i.e., the second side, but the electrons lose some energy when passing through the sheet and interact with the polymer material to crosslink the polymer material. This means that the crosslinking level and thus the gel content will be high in the surface area of the first side and gradually decrease in the process of passing through the thickness of the foamable sheet to the surface area of the second side, which produces a crosslinking gradient. In order to compensate and produce a uniform crosslinking level and gel content throughout the thickness of the foamable sheet, the sheet is then passed through the electron beam irradiator again, but the second side is exposed to the same irradiation level, thereby balancing the dose within the thickness of the foam and reaching a uniform crosslinking level within the foam, including in the middle area of the foamable sheet, where the crosslinking levels overlap.
[0007] The foamable sheet irradiated in this manner, after being foamed in an oven, will have a uniform degree of crosslinking throughout the thickness of the material, both in the two surface regions and in the intermediate region between the two surface regions, and a uniform cell size. It is generally desirable to have uniform crosslinking and uniform cell size in the foam, otherwise weak points may form in the foam, which may render the foam unsuitable for use in various applications and may result in inadequacies in other characteristics that may affect the performance of the foam.
[0008] However, patent publication number US20030082364A1 discloses a foam material with variable crosslinking, wherein one side of the foam is subjected to a higher radiation dose than the other side. This foam will have: a first side region with a higher crosslinking amount and a smaller cell size, and a second side region with a lower crosslinking amount and a larger cell size. This document discloses that compared with a foam material with uniform crosslinking, a higher crosslinking amount on one side allows the foam material to be used in combination with a wider range of materials. This document discloses that a foam material with a variable crosslinking amount can have two different crosslinking levels within the material, or a crosslinking gradient within the material, thereby allowing control of a variety of properties, such as heat resistance during molding (allowing the use of plastics with higher melting temperatures), improved compression set properties in the final product, and improved high temperature properties of the final product. In addition, this document discloses that a second crosslinking can also be performed after foaming by irradiation or the like. This allows obtaining foam sheets with lower density without sacrificing the heat resistance required during final application processing (eg, low pressure molding, insert molding, compression molding, etc.).
[0009] Although some useful variable crosslinking methods and benefits are disclosed in US20030082364A1, these methods only include making foams with two regions (e.g., upper and lower sides) and gradients (e.g., the crosslinking level from one side to the other is gradually from high to low or from low to high) with different crosslinking levels. In other words, only foams with two regions of two different gel contents, or only foams with a gradient of gel content are known. Note that each of these examples results in a foam with asymmetric crosslinking levels, gel contents, and cell sizes from one side of the foam to the other.
[0010] While these variably crosslinked foams and conventional foams (having uniform crosslinking) are known in the art, there remains a significant need for foams having additional properties that are not achievable in the above methods alone.
[0011] For example, some end uses require a single foam sheet that can be split in a controlled, uniform manner, thereby obtaining two foam sheets. When attempting to split or tear a foam sheet made by any prior art method, the tear does not propagate uniformly in the core or middle region of the foam, but rather on one side or on the other side, which results in only a portion or a large piece of the foam being separated. For example, in the case of a double-sided foam tape, when removing an adhered article from a wall or other substrate surface, the entire foam sheet can detach from the wall surface, detach from the article surface, or more often tear randomly, which results in uneven foam portions remaining on the wall and the article. In the worst case, a portion of the substrate or article can also be damaged and detached.
[0012] Furthermore, for foams, such as acoustic foams that benefit from an open-cell surface structure, conventional methods for converting a single foam sheet into two foam sheets involve cutting the foam sheet with a blade, rather than physically separating or tearing it, see, for example, patent application EP0286571B1. Longitudinally cutting the foam, for example, results in a uniform open-cell surface profile with minimal variation in thickness, so it is generally advantageous in industry. For example, document EP0286571B1 teaches cutting a closed-cell polyurethane foam board, thereby forming two boards of the same size, each having a surface with a high-density, small-cell structure, and each having a surface with a low-density, large-cell structure, wherein the large-cell structure is cut to produce large open cells. However, even such cut foams do not always show sufficient acoustic properties and other properties sufficient to meet industrial needs, including but not limited to adhesion, water retention, anti-slip properties, and the like.
[0013] Other known methods of splitting foam sheet structures involve laminating each side of the foam to a structural layer and then pulling apart, see for example patent publication GB738494A. In this document, two sheets of tough non-rubber material are bonded to either side of a sponge rubber layer, split longitudinally along the thickness of the sponge rubber to obtain two sheets, each sheet having a tough non-rubber backing sheet fixed to one face of the sponge rubber layer, the exposed surface of the sponge rubber layer having surface pores, the size of which is larger than the size of those pores within the thickness of the sponge rubber layer. However, it is not always necessary to additionally laminate a backing layer on each detached foam sheet, as this affects the overall performance of the product, limits the freedom of design and application, and requires additional process steps and material costs.
[0014] Therefore, there is still a need for improved foam structures and methods of making the same to address many of the problems of the prior art. Such foams should have suitable properties designed for the unique specifications of the specific application of the foam. Summary of the invention
[0015] This summary is provided to introduce a selection of various concepts that are further described below. This summary is neither intended to identify key or essential features of the inventive subject matter nor to limit the scope of the inventive subject matter.
[0016] The invention relates to a closed-cell cross-linked polyolefin foam sheet, a method for splitting a closed-cell cross-linked polyolefin sheet, and a split cross-linked polyolefin foam having a closed-cell skin side and an open-cell split side.
[0017] On the one hand, the closed-cell cross-linked polyolefin foam sheet includes: a first surface area and a second surface area opposite to each other, and an intermediate area located between the first surface area and the second surface area, wherein the ratio of the gel content of the intermediate area to the average gel content of the first surface area and the second surface area is about 75% or less, and the ratio of the average pore size of the intermediate area to the average pore size of the first surface area and the second surface area is about 125% or more.
[0018] On the other hand, the closed-cell cross-linked polyolefin foam sheet includes: a first surface area and a second surface area opposite to each other, and an intermediate area located between the first surface area and the second surface area, wherein the intermediate area has a gel content lower than the average gel content of the first surface area and the second surface area, so that when a splitting force is applied to the closed-cell cross-linked polyolefin foam sheet, controlled tear propagation can be obtained in the intermediate area.
[0019] On the other hand, a method for manufacturing a split cross-linked polyolefin foam sheet includes: manufacturing a cross-linked polyolefin foam sheet having a first surface area and a second surface area opposite to each other, and an intermediate area located between the first surface area and the second surface area, wherein the intermediate area has a gel content lower than the average gel content of the first surface area and the second surface area, and the intermediate area has an average pore size larger than the average pore size of the first surface area and the second surface area; and applying a splitting force to the cross-linked foam sheet so that controlled tear propagation occurs in the intermediate area until the first side of the cross-linked polyolefin foam sheet and the second side of the cross-linked polyolefin foam sheet are separated to obtain two split polyolefin foam sheets.
[0020] On the other hand, a cleaved cross-linked polyolefin foam sheet includes: a skin side having a closed-cell surface; and a cleaved side having an open-cell surface having a peak height of about 150 μm to about 550 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a schematic perspective view of a foamable sheet according to the present invention.
[0022] Figure 2 is Figure 1 The shown foamable sheet is a schematic perspective view of a foam sheet obtained by foaming the foamable sheet.
[0023] Figure 3 is Figure 2 Schematic side cross-sectional view of a foam sheet shown in .
[0024] Figure 4 yes Figure 2-3 A schematic side view of a foam sheet is shown attached to a substrate on one side and being cleaved.
[0025] Figure 5A and 5B yes Figure 2-3 Shown are schematic side views of a foam sheet during and after cleaving, respectively.
[0026] Figure 6 is Figure 2-3 A schematic flow chart of an exemplary splitting operation of the foam sheet of the present invention is shown in FIG.
[0027] Figures 7A-7C This is a graph showing the change in gel ratio of the foam sheet of the present invention depending on the foam density.
[0028] Figures 8A-8C This is a graph showing the change in the cell size ratio of the foam sheet of the present invention depending on the foam density.
[0029] Figures 9A-9C This is a graph showing the change in 50% compression set of the foam sheet of the present invention as a function of foam density.
[0030] Fig.10 is a schematic flow chart of a splitting force intensity detection device according to the present invention.
[0031] Figures 11A-11C This is a graph showing the change in the splitting strength of the foam sheet of the present invention with the foam density.
[0032] Figures 12A-12C This is a graph showing the change in T-peel strength of the foam sheet of the present invention depending on the foam density.
[0033] Fig.13 This is a graph showing the sink depth recovery performance of the foam sheet of the present invention.
[0034] Fig.14 This is a graph showing the change in peak height of the split foam sheet of the present invention as a function of foam density.
[0035] Fig.15 Graph showing the surface roughness of the split foam sheet of the present invention as a function of foam density.
[0036] Fig.16A Graph showing the dynamic coefficient of friction of a split foam sheet of the present invention as a function of foam density.
[0037] Fig. 16B Graph showing the static friction coefficient of the split foam sheet of the present invention as a function of foam density.
[0038] Fig.17 is a graph of the average sound attenuation (sound transmission) of split foam sheets of the present invention as a function of foam basis weight.
[0039] Fig.18 is a graph showing the added water mass (surface water retention) of the split foam sheet of the present invention as a function of foam density.
[0040] Fig.19 is a graph showing the peel strength of the split foam sheet of the present invention as a function of the type of surface tested. DETAILED DESCRIPTION
[0041] Improved polyolefin foam compositions and methods of making the same are disclosed herein, wherein the foam has, for example, a variety of improved structural and mechanical properties both as a single foam sheet and when split into two foam sheets. In a non-limiting example, the foam includes a middle region designed to allow controlled cleavage tear propagation when a threshold cleavage force is applied, such that the first side and the second side of the foam are separated from each other only through the middle region in a consistent and uniform manner, and there is no adverse tearing in the foam outside the region. Also disclosed herein is a method for splitting the foam without cutting.
[0042] Figure 1 1 is a perspective view of a foamable sheet 10 having: a first side A, a second side B, a middle region 12 between sides A and B, a surface region 14A between the middle region 12 and side A, and a surface region 14B between the middle region 12 and side B. In addition, referring to the extrusion direction of the sheet, the machine direction MD (i.e., length dimension), the transverse direction TD (i.e., width dimension), and the Z direction ZD (i.e., thickness dimension) of the foamable sheet 10 are shown. The foamable sheet can be prepared according to various conventional methods known in the art, including extrusion processes, and can include one or more resins, foaming agents, and suitable additives.
[0043] Suitable polymers or resins for use in the foamable sheet include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE); medium density polyethylene (MDPE); high density polyethylene (HDPE); ethylene-vinyl acetate copolymer (EVA); polypropylene (PP); ethylene-propylene-diene monomer copolymer (EPDM), thermoplastic olefin (TPO), thermoplastic elastomer (TPE), and rubber. A single resin may be selected for the foamable sheet, and a blend of two or more resins may be used. Suitable blowing agents may, for example, include azodicarbonamide (ADCA).
[0044] Compared to conventional methods for irradiating foamed sheets, the present invention uses a novel controlled depth crosslinking technology so that each side A and B of the foamed sheet 10 is irradiated at a lower energy set according to the material and effective thickness of the foamed sheet 10. In this case, those electrons entering each side along the opposite direction penetrate the overlapping thickness in the middle region 12 of the foamed sheet before losing energy and stopping moving within the foamed sheet, rather than coming out from the other side surface. The slowing down and final disappearance of high-energy electrons after moving a specific distance within the material can be called the actual range of these electrons. The actual range of those electrons penetrating the foamed sheet 10 from each side is adjusted so that these electrons experience a minimum width or a controlled width overlap region within the middle region 12 before losing their energy, which results in the defined middle region 12 in the foamed sheet 10 having a lower degree of crosslinking than other regions of the foamed sheet 10, such as the surface regions 14A and 14B. Additionally, the location and characteristics of the intermediate region 12, including its gel content, location, and width, can be closely controlled by adjusting variables such as material type, effective thickness, voltage, dose, line speed, and electron beam width.
[0045] For example, to determine the optimal irradiation conditions, the electron beam irradiator can be adjusted to change its voltage (kV) and current (mA) to affect the dose (Mrads), for example, based on the effective thickness (ET) of the foamed sheet 10 and its material type. ET is calculated by multiplying the actual thickness of the foamed sheet (mils) by the density of the material (g / cm 3 ). Other variables that can be adjusted by those skilled in the art are the line speed (m / min) of the foamable sheet 10 passing through the electron beam irradiator, and the scanning beam width (in) of the electrons. For example, if the line speed is increased, the dose (Mrad) can be kept constant and the current (mA) must be adjusted accordingly.
[0046] See also Figure 2After irradiating the foamable sheet 10 using the novel controlled depth crosslinking technique described above, the middle region 12 of the foamable sheet 10 has a lower degree of crosslinking than the surface regions 14A and 14B, and the foamable sheet 10 can then be foamed at or above the activation temperature of the foaming agent. During the foaming process, the foamable sheet 10 will expand along each of the TD, MD and Z directions, thereby producing a foamed body 10A (e.g., a foamed sheet). The foamed body 10A will have a lower gel content in its middle region 12 than in the regions 14A and 14B, and will further have a symmetrical cell size structure with larger cells in the middle region 12 and proportionally smaller cells in the surface regions 14A and 14B, as described in detail below. Importantly, this structure is achieved within a single sheet of the foam 10A, and does not require lamination or coextrusion operations or other post-processing steps of other foams.
[0047] Figure 3 yes Figure 2 The cross section of the foam 10A shown shows a larger cell structure in the middle region 12 after foaming due to the lower degree of crosslinking (and lower gel content) in this region after using the novel controlled depth crosslinking method. The formation of cells can be affected, for example, by the degree of crosslinking of the polymer around the blowing agent within the material, thereby limiting the expansion of gas from the blowing agent during the foaming process. If the degree of crosslinking is uniform throughout the foamable sheet, and the activation of the blowing agent during the foaming process is uniform, the cells will generally expand to similar restricted sizes within the material depending on the degree of crosslinking. However, when using the controlled depth crosslinking technology described herein, the gel content and cell size of the middle region 12 of the foam 10A can be closely controlled and have specific specifications for the surface regions 14A and 14B, including desired performance characteristics. The inventive method allows these specifications and desired properties to be controlled not only for a single piece of the foam 10A, but also for each foam sheet made after splitting the foam in a controlled tear propagation manner.
[0048] For example, for a single sheet of foam 10A made by the method described herein, the foam may have a gel ratio of about 90% or less, preferably about 75% or less, and more preferably about 50% or less. The gel ratio is calculated by comparing the gel content of the middle region 12 with the total average gel content of the surface regions 14A and 14B, as further described in Example 1 of the present application. Alternatively, the gel ratio may be about 15% to about 90%, preferably about 15% to about 75%, and more preferably about 15% to about 50%. When the gel ratio is lower than about 15%, the foam begins to bulge due to the rupture of the cell walls, thereby forming larger bulging cells.
[0049] The thickness of the middle region 12 may also be adjusted to suit the requirements of the foam application, but this thickness typically accounts for about 1 / 3 to about 2 / 3 of the total thickness of the foam.
[0050] The cell size ratio of a single sheet of foam 10A made by the method described herein can be calculated by dividing the cell size difference between the middle region 12 by the total average of the surface regions 14A and 14B, as further described in Inventive Example 2. The cell size ratio may be about 125% or more, preferably about 200% to about 400%, and more preferably about 250% to about 400%.
[0051] The suitable density of the foam prepared according to the method of the present invention may be about 1.5 pcf to about 20 pcf, preferably about 1.5 pcf to about 15 pcf, and more preferably about 2 pcf to about 10 pcf.
[0052] In addition, by setting the gel ratio and cell size ratio described above, the foam 10A can be made to have the desired properties suitable for a wide range of applications. For example, the foam made according to the method of the present invention can have a 50% compression set of less than about 10%, preferably about 3% to about 10%, and more preferably about 4% to about 9%, which cannot be achieved by foams irradiated by standard methods.
[0053] The foam 10A made by the method of the present invention may also have improved sag depth recovery properties relative to standard foams, including an improved degree of recovery of about 55% to about 80% compared to standard foams even after the foam is post-crosslinked to improve its heat resistance, and an improved degree of recovery of about 35% to about 65% compared to standard foams, as detailed in Inventive Example 7. The sag depth of the foam 10A may be, for example, about 35% to about 45% of its initial thickness at 0 hours, and about 4% to about 6% of its initial thickness after 168 hours, as measured according to test standard VDA 237-101-2. In addition, after the polyolefin foam sheet is post-crosslinked so that the gel content in the middle region is about 50% or greater, the degree of recovery of the depression depth of the foam 10A can be about 50% to about 55% of its initial thickness at 0 hours, and about 5% to about 10% of its initial thickness after 168 hours, as measured according to test standard VDA237-101-2.
[0054] In another example, the crosslinking degree or gel content in the middle region 12 can be lower than that in the surface regions 14A and 14B according to the irradiation and the conditions of the foamable sheet 10, so that controlled cleavage tear propagation can be carried out along the middle region 12 of the foam 10A when a threshold cleavage force is applied to the foam sheet 10A. The threshold cleavage force can be determined according to the needs of the final application, for example, the crosslinking degree is adjusted to be high enough to meet the holding strength of the foam tape application, but also low enough to allow uniform cleavage tear propagation along and in the middle region 12 without damaging any substrate or article to which the foam 10A is adhered.
[0055] Figure 4 An example of a foam sheet 10A is shown with side B attached to a substrate S, while the splitting force SF is represented by several exemplary arrows moving along the Z direction or at an acute angle to the side A. After the middle region 12 is split apart by splitting, new open-cell surfaces 22A and 22B are generated, wherein the open-cell surface 22A is located opposite the closed-cell surface A, and the open-cell surface 22B is located opposite the closed-cell surface B.
[0056] Also shown is a tear propagation line 16 of cleavage, which is in a controlled manner within the intermediate region 12 during cleavage of the foam 10A, thereby allowing the side A of the foam 10A to be uniformly peeled away from the side B, ultimately producing two separate foam sheets from the two halves 20A and 20B, when a threshold cleavage force SF is applied, for example, by a user. As described above, the relative degree of crosslinking of the surface regions 14A and 14B and the intermediate region 12 can be set and designed to meet specific application requirements, such as avoiding damage to the substrate S when pulling apart an article bonded to the side A at the threshold cleavage force PF. In contrast, foams made from foamable sheets 10 according to prior art methods, such as when cleaved in the machine direction (MD) or transverse direction (TD) by applying a cleavage force along the Z direction (ZD), will not produce uniform cleavage tear propagation within the material. Instead, the tear 16 will propagate randomly within the material outside of the middle region 12, and may propagate across the surface of either side A or B of the foam 10A, in which case a large piece of the foam may be torn off before the entire side is peeled off. This is particularly troublesome for some foam tape applications where it is desirable to evenly split the foam from one side to the other, or for processes where it is desirable to continuously peel side A from side B to form two foam sheets from one foam sheet.
[0057] Figure 5A Display and Figure 4The concept of the split foam 10A is similar to that shown in the figure, but the difference is that any side of the foam 10A is not fixed to the substrate, so that the foam 10A can be pulled apart by two separate splitting forces SF opposite to each other, thereby obtaining two separate foams 20A' and 20B'. After the middle area 12 is split apart, new open-cell surfaces 22A and 22B are generated, wherein the open-cell surface 22A in the foam 20A' is located opposite to the closed-cell surface A, and the open-cell surface 22B in the foam 20B' is located opposite to the closed-cell surface B.
[0058] The splitting force strength of the foam 10A is measured according to the splitting force strength test method as described in Example 4 of the present invention, and can be set to about 5 lbf to about 35 lbf, preferably about 8 lbf to about 33 lbf, and more preferably about 9 lbf to about 30 lbf. The splitting force strength of the foam of the present invention can be significantly reduced by about 25% to about 80%, preferably about 30% to about 70%, and more preferably about 40% to about 60% compared to a standard foam of comparable density.
[0059] The T-peel strength of the foam 10A is measured according to the T-peel strength test method as described in Example 5 of the present invention, and can be set to about 1 lbf to about 5 lbf, preferably about 1.5 lbf to about 4 lbf, and more preferably about 1.6 lbf to about 3.1 lbf. The T-peel strength of the foam of the present invention can be significantly reduced by about 20% to about 70%, preferably about 30% to about 60%, and more preferably about 40% to about 50% compared to a standard foam of comparable density.
[0060] Figure 6 1 is a schematic flow chart of a manufacturing method 100, showing how to continuously split the foam 10A of the present invention. The foam 10A in the feed roll F can enter a pair of rollers N1 and N2 rotating in opposite directions, for example, as shown in the figure, N1 rotates in the counterclockwise direction and N2 rotates in the clockwise direction. By rotating in opposite directions, it is possible to mechanically split the foam 10A from the sides A and B, for example Figure 5A The splitting force SF shown is used to produce two foam sheets 20A' and 20B', which can be guided out with the help of guide rollers as needed and wound via winders W1 and W2. According to this method, it is not necessary to use or retain any cutting device, because the foam 10A can be split into two halves using only the pressing rollers N1 and N2. In addition, the speed at which the foam 10A is split is fast enough to make this operation part of the in-line foam manufacturing process itself.
[0061] The method of the present invention enables effective controlled tear propagation of cleavage, thereby being used to produce two cleaved foam bodies 20A' and 20B', wherein the average gauge of each cleaved foam body is about 30% to about 70%, preferably about 40% to about 60%, and more preferably about 45% to about 55% of the initial total gauge thickness of the uncleaved foam body 10A. In addition, the respective masses of the cleaved foam bodies 20A' and 20B' can also be about 30% to about 70%, preferably about 40% to about 60%, and more preferably about 45% to about 55% of the initial total mass of the uncleaved foam body 10A. The respective densities of the cleaved foam bodies 20A' and 20B' can also be about 75% to about 125%, preferably about 85% to about 115%, and more preferably about 90% to about 110% of the initial total density of the uncleaved foam body 10A, as described in detail below in Example 8 of the present invention.
[0062] In addition, even if two uniformly symmetrical halves are required, the method of the present invention can achieve a maximum change rate of about 20% (ideally 50%) in standard thickness, a maximum change rate of about 10% (ideally 50%) in mass, and a maximum change rate of about 16% (ideally 100%) in density, as described in detail below in Example 8 of the present invention. The method of the present invention can also achieve a maximum average change rate of only about 5% (ideally 50%) in standard thickness, a maximum average change rate of about 2% (ideally 50%) in mass, and a maximum average change rate of about 6% (ideally 100%) in density, as described in detail below in Example 8 of the present invention.
[0063] After being split apart, the foams 20A' and 20B' can also provide a variety of desired properties. For example, in addition to the gel content, cell size, and open cell structure that can be produced on the surfaces 22A and 22B, the foams 20A' and 20B' can also have favorable physical properties to achieve the additional performance advantages described herein. For example, the peak height of the surfaces 22A and 22B can be about 150 μm to about 550 μm, preferably about 200 μm to about 500 μm, and can be increased in peak height by about 12 times compared to the epidermis (closed cell surface) of a standard foam, and by about 4 times compared to the cut surface (open cell surface) of a standard foam, as described in detail below in Example 9 of the present invention. The surface roughness (Sa) of surfaces 22A and 22B can be about 70 μm to about 150 μm, preferably about 75 μm to about 140 μm, and more preferably about 80 μm to about 135 μm, and the surface roughness can be increased by about 6 times compared with the skin (closed-cell surface) of a standard foam, and by about 1.8 times compared with the cut surface (open-cell surface) of a standard foam, as described in detail below in Example 10 of the present invention.
[0064] The split foams 20A' and 20B' may also provide a coefficient of friction (COF) between the surfaces 22A and 22B of about 1.0 lbf to about 4.5 lbf, preferably about 1.5 lbf to about 4.0 lbf, and more preferably about 1.8 lbf to about 3.5 lbf for static COF; about 1.0 lbf to about 4.0 lbf, preferably about 1.5 lbf to about 3.5 lbf, and more preferably about 1.5 lbf to about 3.0 lbf for dynamic COF. With respect to static COF, it may be increased by about 4.1 times compared to a standard foam skin (closed cell surface) and by about 3.3 times compared to a cut surface (open cell surface) of a standard foam; with respect to dynamic COF, it may be increased by about 4.4 times compared to a standard foam skin (closed cell surface) and by about 3.7 times compared to a cut surface (open cell surface) of a standard foam, as described in detail below in Example 11 of the present invention.
[0065] The split foams 20A' and 20B' may also provide an average sound attenuation of about 5 dB to about 25 dB, preferably about 5 dB to about 20 dB, and more preferably about 8 dB to about 17 dB, through the surfaces 22A and 22B, as measured according to the Sound Propagation Test Method described in Example 12 of the present invention. The split foam surfaces 22A and 22B of the present invention will exhibit better performance than any standard foam skin surface of comparable basis weight, and will have better performance than any standard foam cut surface for basis weights of about 7 g / sqft or greater.
[0066] The split foams 20A' and 20B' can also make the surface water retention performance of surfaces 22A and 22B be 0.010 grams to about 0.050 grams, preferably about 0.015 grams to about 0.045 grams, and more preferably about 0.017 grams to about 0.043 grams, which is measured according to the surface water retention test method described in Example 13 of the present invention; and can achieve an improvement of about 3.9 times compared with the epidermal surface of a standard foam, and an improvement of about 1.5 times compared with the cut surface of a standard foam.
[0067] The split foams 20A' and 20B' can also show excellent adhesive properties on surfaces 22A and 22B, having better adhesive fixing properties than the cut surfaces of standard foams, and comparable properties to the skin surfaces of standard foams. For example, according to the adhesive properties test method, the skin peel strength of the split foam surface can be about 0.95 N / mm or greater, preferably about 1.00 N / mm or greater, and more preferably about 1.10 N / mm or greater, as described in detail below in Example 14 of the present invention.
[0068] Experimental methods
[0069] The following formulations shown in Table 1 were used to prepare foamable sheets and foams for the experiments and examples described below.
[0070] Table 1
[0071] EVA PE PP Raw material type (phr) (phr) (phr) LDPE 100 Lubricants 1.2 Sulfur-based AO 0.17 Lubricants 0.5 catalyst 0.23 Foaming agent AR EVA 100 Lubricants 0.8 Sulfur-based AO 0.17 catalyst 1.2 Foaming agent AR LLDPE 20.0 Cataloy PP 25.0 h-PP 35.0 TPE 20.0 Crosslinking accelerator 3.5 Phenol AO 1.0 Heat Stabilizer 0.5 Sulfur-based AO 0.5 Foaming agent AR
[0072] Wherein EVA is ethylene vinyl acetate copolymer, PE is polyethylene, PP is polypropylene, LDPE is low density polyethylene, LLDPE is linear low density polyethylene, AO is antioxidant, h-PP is homopolymer PP, TPE is thermoplastic elastomer, and AR represents the "required amount" to achieve the target density of the foam known in the art.
[0073] Samples of foamable sheets were prepared based on the formulations shown in Table 1, and crosslinked according to a standard method to obtain a control product with uniform crosslinking in the material, and crosslinked according to the novel controlled depth crosslinking method of the present invention so that the degree of crosslinking in the middle region (i.e., its "core" region) is lower than that in the surface region, and the degree of crosslinking changes gradually. These foamable sheets were then foamed at the activation temperature of the foaming agent, thereby obtaining foam samples with different densities and tested according to the following procedure.
[0074] Example 1 - Gel Ratio
[0075] For each irradiated sample of the foam prepared according to the above experimental method, the gel content of the middle region 12 or "core" region, surface A (surface region 14A) and surface B (surface region 14B) was tested. Using a sharp razor and a pad, each foam sample and control was cut into three layers of equal thickness, thereby separating into separate outer side (A side), middle region / core and outer side (B side) specimens. The crosslinking level of the cut foam samples and control was tested as follows: a sample with a width of 12 mm was prepared, and the inner side had 3 flat grooves, four strips with a width of 3 mm were made, and then cut into appropriate lengths so that the sample weight was 0.047-0.053 g. Then, the weighed crosslinked polyolefin foam (A, in grams) was immersed in 25 mL of xylene at 120° C. for 24 hours. After 24 hours, the contents were filtered through a 200 mesh wire mesh and allowed to stand in a fume hood for at least 12 hours. Subsequently, the sample and the metal mesh were placed in a vacuum oven at 100°C at 15 inHG for 4 hours to vacuum dry the insoluble matter on the metal mesh. The dry weight of the insoluble matter (B, in grams) was measured, and the crosslinking level was calculated according to the following formula:
[0076] Crosslinking level (wt%) = 100 x (B / A).
[0077] The results of side A and side B were averaged to obtain the gel content value of the outside, and then the gel content value of the core area measured was divided by the average gel content of the outside to obtain the ratio of the core to the outside. The results are shown in Tables 2A, 2B and 2C and the corresponding Fig. 7A , 7B and 7C.
[0078] Table 2A
[0079]
[0080] Table 2B
[0081]
[0082] Table 2C
[0083]
[0084] like Fig. 7A , 7B As shown in Figures 7 and 7C, the gel ratios of the controls were all about 100%, indicating that the crosslinking level and gel content within these controls were uniform. However, the gel ratios of the controlled depth crosslinked samples were all significantly lower than the gel ratios of the controls. The gel content ratios achieved by the method of the present invention were from about 15% to about 65%.
[0085] Example 2 - Cell Size Ratio
[0086] For each irradiated sample of the foam prepared according to the above experimental method, the cell size of the middle region 12 or "core" region is detected and compared with the cell size of surface A (surface region 14A) and surface B (surface region 14B). The foam is cut vertically with a sharp razor blade to ensure that the cut surface is intact. A microscope equipped with a detection function (Keyance 3D microscope VHX-6000) is used to observe the cross-section of each area of the foam. In particular, close to the surface, 5 cells are selected from the A side and 5 cells are selected from the B side; the cell size is then detected along the z-direction and the average cell size is determined. In addition, 10 cells are selected from the core area, detected along the z-direction, and the average value is determined. Finally, the difference in cell size between the core area and the surface area is compared and expressed as a ratio (the value of the core area is divided by the total average value of the outer area). The results are shown in Tables 3A, 3B and 3C below and the corresponding Fig. 8A , 8B and 8C.
[0087] Table 3A
[0088]
[0089] Table 3B
[0090]
[0091] Table 3C
[0092]
[0093] like Fig. 8A , 8B As shown in Figures 8 and 8C, the cell size ratios of the control are all about 100%, indicating that the cell size level within the control is uniform. However, the cell size ratios of the controlled depth cross-linked samples are all significantly higher than the cell size ratio of the control, indicating that the cell size in the core is significantly higher than the cell size in the surface area. The cell size ratios achieved by the method of the present invention are from about 220% to about 365%.
[0094] Example 3 - 50% Compression Set
[0095] For each irradiated sample of the foam prepared according to the above experimental method, the 50% compression set was tested according to ASTM D3575. The results are shown in Tables 4A, 4B and 4C and the corresponding Fig. 9A , 9B and 9C.
[0096] Table 4A
[0097]
[0098] Table 4B
[0099]
[0100] Table 4C
[0101] PP foam Sample 1 Sample 2 Sample 3 Reference 1 Reference 2 Density (pcf) 2.6 2.8 2.4 2.1 4.2 50% compression set (%) 34.6 32.7 30 34.6 22.72 average value 34.6 32.7 30.0 34.6 22.7
[0102] like Fig. 9A , 9B As shown in 9C and 9D, the 50% compression set performance of all samples is improved compared to the standard control foam. Fig. 9C As shown, the 50% compression set performance is at least as good or comparable to standard PP foam, so no performance sacrifice is required.
[0103] In addition, for each PE and EVA sample (as shown in Tables 4A and 4B), for each control with the same density, the Fig. 9A and 9B The trend data of , 50% compression set was calculated and compared in Table 4D below. As shown in the table, the 50% compression set of each PE and EVA sample was reduced (improved) by about 45% to about 75% compared to the control product with a given density.
[0104] Table 4D
[0105] Comparison of 50% Compression Set sample(%) Reference substance (%) %reduce PE-Sample 2 7.4 14.5 49% PE-Sample 1 5.9 15.4 62% EVA-Sample 4 5.5 13 58% EVA-Sample 3 4.1 15 73% EVA-Sample 2 3.8 15 75% EVA-Sample 1 8.6 20 57%
[0106] Example 4 - Splitting Force Strength
[0107] For each irradiated sample of the foam prepared according to the above test method, the splitting strength was tested. Fig.10 The splitting force strength test method described below was used to test the splitting force strength using the equipment shown in the figure. Both sides of each foam sample were corona treated, and then a strong pressure-sensitive adhesive was applied to both sides of the foam 10A, thereby converting it into a double-sided foam tape. The foam tape was then cut into 2-inch x 1-inch specimens. Ensuring that the stainless steel of the positioning fixture was clean, the double-sided foam tape 10A was applied to a small stainless steel plate ( Fig.10 The "SS small plate" shown in the figure is applied to the end without the slit and to the side without the indentation. The combination of the small stainless steel plate and the foam tape is then placed in the 2-inch wide slit of the positioning fixture and the legs of the fixture are arranged on the large stainless steel plate ( Fig.10 The small plate is pressed tightly against the large plate and the positioning fixture is removed. The combination of the small stainless steel plate and the foam tape is positioned 1 inch from the end of the large plate. Allow this foam tape to cure for 24 hours. The large plate is then slid onto the platform and the pillars under the platform are inserted into the Instron instrument. The horizontal rod is slid under the small plate into the recessed area and the vertical rod is raised into the gap. The fixture of the Instron instrument clamps the joint piece to the end of the rod and operates at 40 inches / minute in the extension mode, thereby testing the splitting force of the foam sheet sample in the machine direction (MD) and the transverse direction in pounds.
[0108] The results are shown in Tables 5A, 5B and 5C and the corresponding Fig.11A , 11B and 11C.
[0109] Table 5A
[0110]
[0111] Table 5B
[0112]
[0113] Table 5C
[0114]
[0115] like Fig.11AAs shown, regardless of the density of the foam, the force required to split the EVA foam sample is significantly lower than the force required to split the control. Fig. 11B As shown, the same phenomenon is observed for the PE foam samples, although the control with the lowest density shows a slightly lower splitting force strength than the foam samples with significantly higher density. Fig. 11C , the PP foam samples had lower splitting force strength than the control, including the control with slightly lower density. These results show that for a foam with a given density, the foam samples made by the controlled depth crosslinking process of the present invention will always have a lower splitting force strength than the control foam.
[0116] In addition, for each PP, PE and EVA sample (as shown in Tables 11A-11C), for each control with the same density, the Fig. 9A and 9B The trend data of the splitting force strength was calculated and compared in Table 5D below. As shown in the table, the splitting force strength of each PP, PE and EVA sample was reduced (improved) by about 25% to about 80% compared to the control product with a given density.
[0117] Table 5D
[0118] Comparison of splitting strength Sample (lb-f) Reference substance (lb-f) %reduce PP-Sample 1 16.1 22.3 28% PE-Sample 1 21 40 48% PE-Sample 2 21.2 40.2 47% EVA-Sample 4 29.3 58 49% EVA-Sample 3 9.3 37.1 75% EVA-Sample 2 10.3 37.1 72% EVA-Sample 1 11.8 34 65%
[0119] Example 5 - T-peel strength
[0120] For each irradiated sample of the foam prepared according to the above experimental method, the T-peel strength is tested. The test method for testing the T-peel strength is carried out as described below. A 1 inch x 6 inch specimen is cut from each foam sample. In the case of a foam sample prepared by controlled depth crosslinking (having a large cell size in the core area), the sample material is manually split into about 1 inch to partially split the sample; or in the case of the control, a razor is used to perform this operation. The two ends obtained from the partial splitting are clamped with an Instron clamp, and the Instron instrument is operated at 10 inches / minute in the extension mode for 3 inches, thereby testing the maximum force required to split the foam into two halves, in pounds. It was observed that the foam sample prepared by controlled depth crosslinking continued to split consistently and evenly over the entire 3 inches, while the control was unevenly torn shortly after the start of stretching.
[0121] The results are shown in Tables 6A, 6B and 6C and the corresponding Fig. 12A , 12B and 12C.
[0122] Table 6A
[0123]
[0124] Table 6B
[0125]
[0126] Table 6C
[0127]
[0128] like Fig. 12A As shown in Figure 2, the T-peel strength of the EVA foam samples is significantly lower than that of the control, especially when the density of the foam increases. Fig. 12B As shown, the same phenomenon is observed for the PE foam samples, but the lowest density control shows slightly lower T-peel strength compared to the foam samples with significantly higher density. Fig. 12C , the PP foam samples had lower T-peel strengths than the control, including the control with slightly lower density. These results indicate that for a foam with a given density, the foam samples made by the controlled depth crosslinking process of the present invention will always have lower T-peel strengths than the control foam and show controlled tear propagation that is not achievable with the control foam.
[0129] In addition, for each PP, PE and EVA sample (as shown in Tables 12A-12C), for each control with the same density, the Fig. 9A and 9B The trend data of the T-peel strength was calculated and compared in Table 6D below. As shown in the table, the T-peel strength of each PP, PE and EVA sample was reduced (improved) by about 25% to about 70% compared to the control product with a given density.
[0130] Table 6D
[0131] Comparison of T-peel strength Sample (lb-f) Reference substance (lb-f) %reduce PP-Sample 1 2.7 3.6 25% PE-Sample 1 2.3 5.1 54% PE-Sample 2 2.7 6.0 55% EVA-Sample 4 3.1 10 69% EVA-Sample 3 1.7 3.2 47% EVA-Sample 2 1.6 3.2 50% EVA-Sample 1 1.9 1.9 0%
[0132] Example 6 - Post-crosslinking: Heat resistance
[0133] For each irradiated sample of the foam prepared according to the above experimental method, the heat resistance was tested. EVA foam samples were prepared by a controlled depth crosslinking process, and post-crosslinked (post-XL) samples were prepared by subjecting these EVA foam samples to post-foaming irradiation until their core region had a gel content of at least 50%. These samples were compared with standard EVA control foams of comparable density to determine their ability to withstand 21 seconds of extreme heating in a thermoformer, in which the surface temperature of the foam reached about 225°C. The results are shown in Table 7 below.
[0134] Table 7
[0135]
[0136] The EVA control foam shows an area where surface degradation occurs, indicating that the heat is higher than the maximum processing temperature of the foam. The EVA foam sample (core with lower gel content) not only has surface degradation, but also has severe bubbling on the entire surface. Bubbling is caused by the rupture of large cells, and multiple cells merge into larger cells, which is manifested as bubbling under the surface. This happens with EVA foam samples because there is less gel in the core area and it is too fragile to be heat-resistant. However, the post-crosslinked (post-XL) EVA foam sample receives an additional dose of irradiation, which strengthens the foam in the core area and increases the gel content in the core area while maintaining a large cell structure. As a result, this foam unexpectedly no longer bubbles, but only shows surface degradation due to excessive heat, which is more similar to the standard EVA control foam. Therefore, the controlled tear propagation and other performance advantages of the foam sample can be maintained, and at the same time, heat resistance characteristics are imparted to the foam via post-crosslinking.
[0137] Example 7 - Post-crosslinking: Depression depth recovery performance
[0138] For each irradiated sample of the foam prepared according to the above experimental method, the sag depth recovery performance was tested. EVA foam samples were prepared by a controlled depth crosslinking method and these EVA foam samples were irradiated after foaming until their core area had a gel content of at least 50%, thereby preparing post-crosslinked (post-XL) samples. These samples were compared with standard EVA control foams of comparable density, and their sag depth recovery performance after 24, 48 and 168 hours was tested by automotive test standard VDA237-101-2. The results are shown in Table 8A below.
[0139] Table 8A
[0140]
[0141] Fig.13 8 is a graph of the 2kg dent depth recovery performance shown in Table 8. It can be seen that the EVA samples (including the post-crosslinked EVA samples) show superior dent depth recovery performance than the standard EVA control foam, while the post-crosslinked samples are only slightly lower than the uncrosslinked EVA samples. Therefore, the foam samples prepared by the method of the present invention are able to largely maintain the mechanical and performance characteristics of these samples even after being given the advantage of post-crosslinking.
[0142] In addition, the degree of improvement in the recovery of the dent depth was compared between the EVA control foam and the EVA foam sample, and between the EVA control foam and the EVA foam sample (+Post-XL), and the results are shown in Table 8B below.
[0143] Table 8B
[0144]
[0145] As can be seen from Table 8B, the EVA samples improved indentation depth recovery by about 55% to about 80% compared to the control, while the post-crosslinked EVA samples improved indentation depth recovery by about 35% to about 65%.
[0146] Example 8 - Standard Thickness, Mass and Density of Split Foam
[0147] For foam samples prepared by controlled depth crosslinking according to the above test method, the standard thickness (gauge) and mass are measured before and after being split apart to evaluate the foam samples split by controlled tear propagation to the middle / core region of the foam (see, for example, Figure 4-6 ) in terms of standard thickness, mass and density calculations. Use a calibrated balance to check the mass and a calibrated micrometer to check the standard thickness.
[0148] Ten 4" x 4" specimens are cut from the center of the foam sheet sample at 1" intervals along the machine direction. The standard thickness and mass are measured and used to calculate the density of each specimen. Each specimen is then split into A and B sides under controlled tear propagation. The standard thickness and mass of each A and B side of the split foam specimen are then measured and the corresponding density is calculated. Because the foam specimen may undergo some deformation under the splitting force, the standard thickness is measured from the non-deformed area of the split foam.
[0149] In the cross direction, cut 10 4" x 4" specimens at even intervals across the width of the foam sheet sample; for sheets too narrow to get 10 specimens, take as many specimens as the sheet size allows (7 specimens for 8 pcf PE foam sample, 8 specimens for 6.5 pcf EVA foam sample). Take the first and last specimens from the extreme edge of the foam sheet. In addition, take the standard thickness and mass of the foam before and after splitting in the same manner as described above for the machine direction, and calculate the density.
[0150] The standard thickness, mass and density of all specimens of each foam sample were then averaged and the values were compared before and after splitting the foams. A comparison of the machine direction (MD) is provided in Table 9A below and a comparison of the cross direction (CM) is provided in Table 9B below. Each value represents a percentage of the initial unsplit foam sample so that a perfectly uniformly split foam would produce an ideal A-side average and B-side average standard thickness and mass for each side that is as close to 50% of the initial unsplit sample as possible and a density as close to 100% as possible. The maximum rate of change of the sample compared to the ideal value was also determined and is shown in Tables 9A, 9B below, and the average rate of change of the sample compared to the ideal value is shown.
[0151] Table 9A
[0152]
[0153] Table 9B
[0154]
[0155] In some cases, dimensional deformation in the foam samples produced some minor inconsistencies in the standard thickness detection, resulting in the total of the A side and the B side sometimes not equal to 100%. Since density is a function of the standard thickness and mass, the density calculation is also affected in this case. However, based on the number of specimens studied, these data are actually of high confidence.
[0156] As can be seen from Tables 9A and 9B, the maximum variation rate of the standard thickness of the split foam sample is 16%, but the average value is only up to 5%. Regarding mass, the maximum variation rate of the split foam sample is 7%, but the average value is only up to 2%. Regarding density, the maximum variation rate of the split foam sample is 14%, but the average value is only up to 6%. Therefore, the foam sample prepared by the above experimental method has highly consistent tear propagation in the foam core, which makes the A side and the B side have extremely small average variation rates in standard thickness, mass and density, so the method of the present invention is very suitable for large-scale production of foams, for example, see Figure 6 .
[0157] Example 9 - Peak Height
[0158] For the foam samples prepared by controlled depth crosslinking according to the above experimental method, 3D microscopy was used to evaluate the surface peak height. Figure 4-6 Foam samples that were split by controlled tear propagation into the middle / core region of the foam were examined at the new open cell surfaces (e.g., 22A and 22B, e.g., Figure 5A and 5BThe peak height on the surface of the standard foam sample cut by a blade is measured. In addition, as a control, the surface on the skin side (closed cell surface, such as Figure 5A and 5B The peak heights were determined by measuring the peak heights on the sides A and B in Figure 10A. A Keyence 3D microscope VHX-6000 was used to determine the peak heights, where each sample was placed under the microscope and a 5 mm x 5 mm area was scanned using a built-in function. The base height was established by taking the average of the entire height within the scanned area. A local peak was selected and the peak height was measured relative to the established base height using the microscope function. The results are shown in Tables 10A, 10B and 10C below for the foam samples with various densities tested and are also plotted as Fig.14 .
[0159] Table 10A
[0160]
[0161] Table 10B
[0162]
[0163] Table 10C
[0164]
[0165] From the test results and Fig.14 It can be seen that the cleaved foam open cell surface of each sample has a significantly higher average peak height than the cut surface or skin surface of the corresponding foam. Comparing these average peak heights, the cleaved surface of the foam is about 11.8 times higher than the skin, and about 4.1 times higher than the cut surface of the foam.
[0166] Example 10 - Surface Roughness
[0167] For the foam samples prepared by controlled depth crosslinking according to the above experimental method, the surface roughness was measured using a 3D microscope. Figure 4-6 Foam samples that were split by controlled tear propagation into the middle / core region of the foam were examined at the new open cell surfaces (e.g., 22A and 22B, e.g., Figure 5A and 5B The surface roughness of the surface on the surface side (as shown in FIG. 1 ) was measured, and the surface roughness of the same surface of the standard foam sample cut by a blade was measured. In addition, as a control, the surface on the skin side (the closed-cell surface, for example, Figure 5A and 5BThe surface roughness was measured on the sides A and B in the figure. A Keyence 3D microscope VHX-6000 was used to determine the surface roughness, where each sample was placed under the microscope and a 5 mm x 5 mm area was scanned using the built-in function, and the roughness value Sa was calculated using the surface area measured by the microscope. Sa is the arithmetic mean of the surface roughness and is an extension of the arithmetic mean height of Ra for a line. The value is an absolute value and represents the difference between the height of each point and the arithmetic mean of the surface. For the foam samples with various densities tested, the results are shown in the following Tables 11A, 11B and 11C, and are also plotted as Fig.15 .
[0168] Table 11A
[0169]
[0170] Table 11B
[0171]
[0172]
[0173] Table 11C
[0174]
[0175] From the test results and Fig.15 It can be seen that the cleaved foam open cell surface of each sample has a significantly higher surface roughness than the cut surface or skin surface of the corresponding foam. Comparing these average surface roughnesses, the cleaved surface of the foam is about 6 times higher than the skin, and about 1.8 times higher than the cut surface of the foam.
[0176] Example 11 - Coefficient of Friction (CQF)
[0177] For the foam samples prepared by controlled depth crosslinking according to the above experimental method, their coefficient of friction (COF) was measured according to ASTM D1894, which includes dynamic COF and static COF. Figure 4-6 A foam sample that has been split by controlled tear propagation into the middle / core region of the foam is examined for the difference between the new open cell surface and the opposite open cell surface (e.g., 22A versus 22B, e.g., Figure 5A and 5B The COF on the surface of the foam sample was measured and the COF on the same opposite surface of the standard foam sample was measured by cutting with a blade. In addition, as a control, the COF on the opposite skin side (closed cell surface, such as Figure 5A and 5BThe COF on side A relative to side B in FIG. 12A . For the foam samples having various densities tested, the results are shown in Tables 12A, 12B and 12C below and are also plotted as Fig.16A and 16B .
[0178] Table 12A
[0179]
[0180] Table 12B
[0181]
[0182] Table 12C
[0183]
[0184] From the test results and Fig.16A and 16B It can be seen that the split foam open-cell surface of each sample has a significantly higher COF, including static COF and dynamic COF, compared with the cut surface or skin surface of the corresponding foam. Comparing their average static COF, the split surface of the foam is about 4.1 times higher than the skin, and about 3.3 times higher than the cut surface of the foam. Comparing their average dynamic COF, the split surface of the foam is about 4.4 times higher than the skin, and about 3.7 times higher than the cut surface of the foam.
[0185] Example 12 - Sound Propagation Performance
[0186] For foam samples prepared by controlled depth crosslinking according to the above test method, their sound transmission properties were evaluated to determine the average sound attenuation achieved by the foam. Figure 4-6 A foam sample is split using controlled tear propagation to the middle / core region of the foam and the cross section of the newly opened cell surface (e.g., 22A or 22B, such as Figure 5A and 5B The average sound attenuation of the surface (shown in Figure 1) was measured, and the average sound attenuation of the same surface of the standard foam sample cut by a blade was measured. In addition, as a control, the surface side (closed cell surface, such as Figure 5A and 5B The average sound attenuation on side A or side B in FIG.
[0187] The sound propagation test is performed as described below. Two PVC tubes of 4 inches in length x 12 inches in diameter are prepared. One end of the two tubes is closed with a 1 inch thick wooden piece. A 3 / 4 inch diameter hole is drilled in the center of one wooden piece. The tube without the drilled hole is placed on the table with the wooden piece facing down. A Bluetooth speaker is placed in the center of the first tube, facing up. A 12 inch x 12 inch foam sample is placed on the opening of the first PVC tube, with the surface to be tested facing the speaker. A second PVC tube with a drilled hole is used to clamp the sample, with the wooden piece facing up. A decibel meter is inserted through the hole on the top, located about 3 inches above the foam sample. An audio signal in the range of 1000 Hz to 20,000 Hz is transmitted using the audio signal transmitter application software at intervals of 1000 Hz, and the decibel value passing through the foam sample is recorded, ensuring that the volume is not too loud to avoid exceeding the effective functional range of the decibel meter. This process is then repeated without the use of the foam sample, thereby obtaining a baseline control test value. Once the data is collected, a best fit line is generated from these data to obtain a formula. Using this formula, calculate the dB at 1000 Hz and 20000 Hz, then subtract the baseline value from the sample test value to obtain the sound attenuation value. Then, calculate the average sound attenuation value, thereby obtaining a numerical value representing the sound attenuation level of the tested sample. Then, plot the average sound attenuation value against the calculated basis weight value of each foam sample.
[0188] The results of the average sound attenuation for the foam samples having various basis weights tested are shown below in Tables 13A, 13B and 13C and are also plotted as Fig.17 .
[0189] Table 13A
[0190]
[0191] Table 13B
[0192]
[0193] Table 13C
[0194]
[0195] From the test results and Fig.17 As can be seen, for all basis weights of the foam, the split open cell surface samples have superior average sound attenuation performance compared to the standard skin surface of the foam. At foam basis weights of about 7 g / sqft or greater, the split foam surface has superior average sound attenuation performance compared to the cut standard foam.
[0196] Example 13 - Surface water retention performance
[0197] For the foam samples prepared by controlled depth crosslinking according to the above experimental method, their surface water retention properties were evaluated. Figure 4-6 A foam sample that has been split by controlled tear propagation into the middle / core region of the foam is examined at the new open cell surface (e.g., 22A or 22B, such as Figure 5A and 5B The surface water retention performance of the foam sample was measured on the surface of the foam sample (shown in FIG. 1 ), and the surface water retention performance of the foam sample was measured on the same surface of the foam sample cut by a blade. In addition, as a control, the surface water retention performance of the foam sample on the surface of the skin (closed cell surface, such as Figure 5A and 5B Surface water retention performance on side A or side B).
[0198] The surface water retention test was conducted as follows. 4 inch x 4 inch foam specimens and shallow pans of water were prepared. The dry weight of each specimen was weighed and then the specimen side to be tested was placed in the water to allow it to float. The specimens were allowed to float for 45 seconds. During this time, each specimen was passed across the surface of the water with pliers to ensure that any trapped air within the specimen escaped, while ensuring that no water was on the dry side. After 45 seconds, the specimen was removed from the water and placed on a balance, dry side down, whereupon the new mass was weighed, which included the water retained by the specimen. The masses before and after were compared, whereby the amount of water retained on the surface of each specimen was calculated.
[0199] The results of the average surface water retention for the foam samples having various densities tested are shown in Tables 14A, 14B and 14C below and are also plotted as Fig.18 .
[0200] Table 14A
[0201]
[0202]
[0203] Table 14B
[0204]
[0205] Table 14C
[0206]
[0207] From the test results and Fig.18As can be seen, the cleaved foam is able to retain more water on its surface than a standard skin or cut surface of the foam. This result is interesting in part because even though the cut foam would present an open-cell surface, the specific surface characteristics of the cleaved foam open-cell surface allow it to exhibit superior water retention, potentially resulting from the peak height and surface roughness as described in the above examples. Comparing these overall average water retention properties, the cleaved foam surface is able to retain about 3.9 times more water than the skin surface of the foam and about 1.5 times more water than the cut surface of the foam.
[0208] Example 14 - Adhesion Test
[0209] For the foam samples prepared by controlled depth crosslinking according to the above experimental method, their adhesive properties were evaluated. Figure 4-6 A foam sample that has been split by controlled tear propagation into the middle / core region of the foam is examined at the new open cell surface (e.g., 22A or 22B, such as Figure 5A and 5B The adhesion performance on the surface of the foam sample was tested and the adhesion performance on the same surface of the standard foam sample was tested by cutting with a blade. In addition, as a control, the adhesion performance on the skin side (closed cell surface, such as Figure 5A and 5B Adhesion performance on side A or side B).
[0210] Adhesion tests were performed as described below. Three specimens were cut along the MD direction across the width of the foam sample, measuring 350 mm x 50 mm. Both surfaces were then corona treated. Samples with a density below 3.2 pcf did not require this treatment. Samples with a density greater than 12.5 pcf were not tested. A pressure-sensitive double-sided tape was prepared using a Coatema coater with KS900 as the release liner. 65 g / m 2Collano T21434. The foam sample is applied to both sides of the double-sided tape while avoiding any air retention. The adhesive is rolled twice with a 5kg roller at a uniform speed of 600mm / min. These samples are cut into 300mm x25mm with a mold. The release liner is removed from one side, and a Mylar PET film with a thickness of 0.019mm is placed, and then rolled twice with a roller as described above. A chrome-nickel flat plate (50mm x 210mm) is cleaned (only along the length direction) with 600 sandpaper, and any shavings, grease, etc. are removed with lint-free paper soaked in benzene. About 11cm of the other release liner is removed from the sample, and placed so that the open adhesive side is located on a cleaned metal plate. Starting from the edge of the sample located at the edge of the clean metal plate, it is rolled 4 times with a roller as described above. Then, the sample is allowed to stand for 24 hours. Subsequently, the load chamber is mounted on a tensile measuring instrument, and the distance of the fixture is 170mm. For a sample with high density, peeling is started manually by rapid movement. The free end of the metal plate is mounted in a fixture without a load chamber, and the free end of the specimen is mounted in a fixture with a load chamber. The peel strength is measured and recorded at a rate of 300 mm / min in N / mm, while the peeling position in the specimen is observed.
[0211] For each foam sample tested, the results of the adhesion tests are shown in Table 15 below and are also plotted as Fig.19 .
[0212] Table 15
[0213]
[0214] Regarding the failure mode, foam tearing indicates a situation where the foam itself tears, while foam adhesive failure indicates failure at the interface between the foam and the adhesive tape, which is a sign that the adhesive is not well fixed to the foam. These test results show that the adhesive is not well fixed to the cut surface; while the cleaved side of the foam causes the foam to tear, which indicates a strong adhesive fixation effect. In addition, the cleaved open surface shows approximately the same performance as the skin side, but is superior to the cut surface. Therefore, the cleaved foam surface obtained by the method of the present invention can be well used in adhesive tape applications.
[0215] Although the present invention has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the scope of the invention, and that factors in the present invention may be replaced by equivalents. In addition, many modifications may be made without departing from the basic scope of the invention to make the present invention suitable for use in specific situations or materials. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and the present invention will be included in all embodiments within the scope of the appended claims.
Claims
1. A closed-cell cross-linked polyolefin foam sheet, comprising: A first surface area and a second surface area opposite to each other, and an intermediate area located between the first surface area and the second surface area, wherein the ratio of the gel content of the intermediate area to the average gel content of the first surface area and the second surface area is about 75% or less, and the ratio of the average pore size of the intermediate area to the average pore size of the first surface area and the second surface area is about 125% or more.
2. The closed-cell cross-linked polyolefin foam sheet according to claim 1, wherein a ratio of a gel content in the middle region to an average gel content in the first surface region and the second surface region is about 50% or less.
3. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the ratio of the average cell size of the middle region to the average cell size of the first surface region and the second surface region is about 200% to about 400%.
4. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the ratio of the average cell size of the middle region to the average cell size of the first surface region and the second surface region is from about 250% to about 400%.
5. The closed-cell cross-linked polyolefin foam sheet according to claim 1, wherein the 50% compression set is about 10% or less.
6. The closed-cell cross-linked polyolefin foam sheet as claimed in claim 1, wherein the depression depth of the closed-cell cross-linked polyolefin foam sheet is about 35% to about 45% of its initial thickness at 0 hours and about 4% to about 6% of its initial thickness after 168 hours, as measured according to test standard VDA237-101-2.
7. The closed-cell cross-linked polyolefin foam sheet as described in claim 1, wherein after the closed-cell cross-linked polyolefin foam sheet is post-cross-linked so that the gel content in the middle region is about 50% or greater, the closed-cell cross-linked polyolefin foam sheet has a depression depth of about 50% to about 55% of its initial thickness at 0 hours and about 5% to about 10% of its initial thickness after 168 hours, as tested according to test standard VDA237-101-2.
8. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the density is from about 1.5 pcf to about 15 pcf.
9. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the density is from about 2 pcf to about 10 pcf.
10. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the splitting force strength measured according to the splitting force strength test method is about 5 lbf to about 35 lbf.
11. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the splitting force strength measured according to the splitting force strength test method is about 8 lbf to about 33 lbf.
12. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the splitting force strength measured according to the splitting force strength test method is about 9 lbf to about 30 lbf.
13. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the T-peel strength measured according to the T-peel strength test method is about 1 lbf to about 5 lbf.
14. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the T-peel strength measured according to the T-peel strength test method is about 1.5 lbf to about 4 lbf.
15. The closed-cell cross-linked polyolefin foam sheet of claim 1, wherein the T-peel strength measured according to the T-peel strength test method is about 1.6 lbf to about 3.1 lbf.
16. A closed-cell cross-linked polyolefin foam sheet comprising: A first surface area and a second surface area relative to each other, and an intermediate area located between the first surface area and the second surface area, wherein the intermediate area has a gel content lower than the average gel content of the first surface area and the second surface area, so that controlled tear propagation in the intermediate area can be obtained when a splitting force is applied to the closed-cell cross-linked foam sheet.
17. The closed-cell cross-linked polyolefin foam sheet according to claim 16, wherein the ratio of the gel content of the middle region to the average gel content of the first surface region and the second surface region is from about 15% to about 75%.
18. The closed-cell cross-linked polyolefin foam sheet of claim 16, wherein the ratio of the gel content of the middle region to the average gel content of the first surface region and the second surface region is from about 15% to about 50%.
19. The closed-cell cross-linked polyolefin foam sheet of claim 16, wherein the ratio of the average cell size of the middle region to the average cell size of the first surface region and the second surface region is about 125% or more.
20. The closed-cell cross-linked polyolefin foam sheet of claim 16, wherein the 50% compression set is from about 3% to about 10%.
Citation Information
Patent Citations
Improved sound absorption in foam core panels and their method of manufacture
EP0286571B1
Foam sheet and a method to manufacture a foam sheet
US20030082364A1